EVALUATION OF THE IMPLEMENTATION OF POST-PANDEMIC PHYSICAL EDUCATION, SPORTS AND HEALTH EDUCATION LEARNING IN CENTRAL SEMARANG PRIVATE JUNIOR HIGH SCHOOLS - nuridin, rahmat_sugandi; Rahardjo, Hermawan Pamot; Setyawati, heny (Universitas Negeri Semarang, 2025)
This study aims to evaluate the implementation of PJOK learning in Central Semarang Private Junior High School using the Context, Input, Process, and Product (CIPP) model. The evaluation model in this study is the CIPP model. The subjects of this study are school principals, PJOK teachers, and parents of students at Central Semarang Private Junior High School. The sampling technique uses purposive sampling, with details of 15 school principals, 15 PJOK teachers, and 15 parents of students. The data collection technique uses observation, interview, questionnaire, and documentation methods. The data analysis techniques in this study are quantitative and qualitative descriptive analysis. The results of the study showed that the evaluation of the implementation of PJOK learning at Central Semarang Private Junior High School was 90% in the very good category. Based on each evaluation component, the following conclusions were obtained. (1) The context of the evaluation of the implementation of PJOK learning at Central Semarang Private Junior High School was 93% in the very good category. The indicator of teaching skills is 97% in the very good category and 89% in the good category. (2) Input Evaluation of the implementation of PJOK learning at Central Semarang Private Junior High School is 86% in the very good category. The teacher profile indicator is 89% in the very good category, while the student profile indicator is 82% in the good category and the learning infrastructure is 85% in the good category. (3) The evaluation process of the implementation of PJOK learning at Central Semarang Private Junior High School was 88% in the very good category. The syllabus indicator is 93% in the very good category, the implementation of learning is 87% in the very good category, while the RPP indicator is 85% in the good category. (4) The product evaluation of the implementation of PJOK learning at Central Semarang Private Junior High School was 93% in the very good category. The evaluation indicators of the learning process were 91% in the very good category and 95% in the very good category.